Chromosomal Mapping of Tandem Repeats Revealed Massive Chromosomal Rearrangements and Insights Into Senna tora Dysploidy - Waminal, Nomar Espinosa; Pellerin, Remnyl Joyce; Kang, Sang-Ho; Kim, Hyun Hee (Frontiers in Plant Science, 2021)
Tandem repeats (TR) can occupy a large portion of plant genomes and can either cause or result from chromosomal rearrangements, which are important drivers of dysploidy-mediated karyotype evolution and speciation. To understand the contribution of TRs in shaping the extant Senna tora dysploid karyotype, we analyzed the composition and abundance of TRs in the S. tora genome and compared the chromosomal distribution of these TRs between S. tora and a closely related euploid, Senna occidentalis. Using a read clustering algorithm, we identified the major S. tora TRs and visualized their chromosomal distribution by fluorescence in situ hybridization. We identified 10 independent repeats covering ~91 Mb or ~13% of the S. tora genome. The unit lengths and copy numbers had ranges of 7–5,833 bp and 325–2.89×106, respectively. Of the 10 repeats, eight were independent TRs and two were fragments of long terminal repeat retrotransposons. Three other TRs were found in the 45S rDNA intergenic spacer, one of which was also detected at an extra-NOR locus. The canonical plant telomeric repeat (TTTAGGG)n was also detected as very intense signals in numerous pericentromeric and interstitial loci. StoTR05_180, which showed subtelomeric distribution in Senna occidentalis, was predominantly pericentromeric in S. tora. The unusual chromosomal distribution of TRs in S. tora not only enabled easy identification of individual chromosomes but also revealed the massive chromosomal rearrangements that have likely played important roles in shaping its dysploid karyotype.